Correlation of 99mTc Sucralfate scan and endoscopic grading in caustic oesophageal injury: An observational analytic study at Red Cross War Memorial Children’s Hospital - Nondela, Babalwa Bukeka (Division of Paediatric Surgery, 2019)
Introduction: Technecium (Tc) 99m Sucralfate scan has been shown to be a reliable and non-invasive screening modality after caustic substance ingestion, followed by oesophagoscopy under general anaesthesia to grade the extent and severity of injury. Aim: To determine a correlation between the 99mTc Sucralfate scan and the endoscopy findings in children presenting with caustic oesophageal injury. Methods: An observational analytic study of children who had both 99mTc Sucralfate scan and endoscopy after caustic substance ingestion at Red Cross War Memorial Children’s Hospital in a period between January 2009 and September 2016. The oesophageal injury was classified into low grade and high grade according to the degree of adhesion on 99mTc Sucralfate scan and modification of Zargar endoscopic grading. Approval of the study by the University of Cape Town Faculty of Health Sciences Human Research Ethics Committee was obtained, REF. 049/2017. Results: Out of a total of 197 children, 40 children were identified who had both investigations done on average 26hours post injury. Low grade adhesion on 99mTc Sucralfate scan was found in 27 children (68%), and all had low grade Zargar’s oesophageal injuries. None of these subsequently developed residual pathology. Thirteen had high grade adhesion and five of these had high grade injury on endoscopy. Three (23%) developed oesophageal strictures. Correlation of 99mTc Sucralfate and endoscopic findings reached statistical significance with a p-value of 0.0014. No morbidity was associated with either the scan or endoscopy. Conclusions: Low grade Sucralfate scan finding has potential to successfully eliminate the need for invasive endoscopy under general anaesthesia and thereby reducing procedure related morbidity, hospitalization and associated costs. However, mandatory endoscopy is required in children with high grade adhesion seen on 99mTc Sucralfate scan. This requires confirmation using a larger prospective study.